Preparation and Investigation of Flexural Strength and Impact Strength for Nano Hybrid Composite Materials of the Tri- Polymeric Blend used in Structural Applications - Sihama I. Salih; Wleed Salih; Mustafa Mohammed (Engineering and Technology Journal, 2018)
Current work is aimed to preparation the nanocomposites laminatesof low density and good durability to use in structural applications. So, in thispaper, the preparation and compare of some mechanical properties of twogroups of tri-polymer blends composites consisting of ((93% unsaturatedpolyester resin (UP)+(5%PMMA) (Poly methyl methacrylate)+2%NR(Natural Rubber)) as the matrix materials. Added the reinforce materials(silica (SiO2) and zirconia (ZrO2) nanoparticles) individually, with differentvolume fraction of (0, 0.5, 1, 1.5%) to the ternary polymer blends accordingto the following formula:- [((100-X) (93%UP)+2%NR+5%PMMA): (X%SiO2or X% ZrO2)] The first group is composed of matrix material reinforced withzirconia (ZrO2) nanoparticles with average diameter of nanoparticles(56.88nm) and the second group is composed of matrix material reinforcedwith silica (SiO2) nanoparticles with average diameter of nanoparticles(24.59nm). Then used as a matrix material for the preparation of hybridlaminar composites materials, reinforcement with one and two layers ofwoven carbon fibers The research included the study of the influence ofvolume fraction of nanoparticles on some of mechanical and physicalproperties like flexural strength, flexural modulus impact strength, and impactfracture toughness, in addition to test infrared spectroscopy (FTIR) and all ofthese tests were carried out at laboratory temperature. Search results haveshown that the values of (flexural modulus and impact strength and fracturetoughness) increases with the increase of the nanoparticles ratios in polymerblend nano composite of prepared samples. While flexural strength valuedecreases with the increase in the volume fraction of nanoparticles in polymerblend nano composite. The fracture energy of the of hybrid laminarcomposites is higher than those containing only the nanoparticles powders.Morphology test by scanning electron microscope indicates that a goodadhesion or interfacial interactions between the Nano powders particles,carbon fibers and components of ternary polymer blend. Which results inhigher the carbon fibers efficiency factor, and hence higher mechanicalstrength. So, the hybrid laminar nano composites, which appear high flexuralmodulus and impact strength and fracture toughness, can be foreseen toprovide valuable contribution to high performance structural applications.